2012
DOI: 10.1186/1471-2164-13-136
|View full text |Cite
|
Sign up to set email alerts
|

A second generation framework for the analysis of microsatellites in expressed sequence tags and the development of EST-SSR markers for a conifer, Cryptomeria japonica

Abstract: BackgroundMicrosatellites or simple sequence repeats (SSRs) in expressed sequence tags (ESTs) are useful resources for genome analysis because of their abundance, functionality and polymorphism. The advent of commercial second generation sequencing machines has lead to new strategies for developing EST-SSR markers, necessitating the development of bioinformatic framework that can keep pace with the increasing quality and quantity of sequence data produced. We describe an open scheme for analyzing ESTs and deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
35
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 69 publications
11
35
3
Order By: Relevance
“…Predominance of trimers in Picea abies [16] and Pinus taeda [17] was reported earlier only in two studies, likewise Yan et al [25] demonstrated higher frequency of trimers it in Pinus spp. Abundance of hexamers in gymnosperms is in accordance with earlier results in Picea [15, 16], Pinus [15], and Cryptomeria [36], as well as in comparative studies, which report hexamers to be more common among EST-SSRs in gymnosperms than angiosperms [14, 18]. The estimation of hexamer repeats was however under-estimated in earlier studies [14, 15], as a consequence of analysing only class I SSRs, whereas the current analysis reveals that there is very high abundance of hexamer repeats if class II SSRs are also taken into consideration (1100 and 971 per Mbp in spruce and pine, respectively).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Predominance of trimers in Picea abies [16] and Pinus taeda [17] was reported earlier only in two studies, likewise Yan et al [25] demonstrated higher frequency of trimers it in Pinus spp. Abundance of hexamers in gymnosperms is in accordance with earlier results in Picea [15, 16], Pinus [15], and Cryptomeria [36], as well as in comparative studies, which report hexamers to be more common among EST-SSRs in gymnosperms than angiosperms [14, 18]. The estimation of hexamer repeats was however under-estimated in earlier studies [14, 15], as a consequence of analysing only class I SSRs, whereas the current analysis reveals that there is very high abundance of hexamer repeats if class II SSRs are also taken into consideration (1100 and 971 per Mbp in spruce and pine, respectively).…”
Section: Discussionsupporting
confidence: 91%
“…Similar results were reported in Physcomitrella patens and Arabidopsis thaliana [18]. However, the GO term with the highest number of genes containing SSR loci in Cryptomeria [36] was cellular process instead of metabolic process as is the case in Pinus taeda and Picea abies . Therefore, we suggest that the GO distribution may be species specific rather than generalised for gymnosperms as such.…”
Section: Discussionsupporting
confidence: 77%
“…A few higher repeat numbers were observed in di- and tri-nucleotide SSRs, but in tetra-, penta-, and hexa-nucleotide SSRs, no repeat number was found beyond 6 (Table 1). Similar trends have also been observed in other plant genomes [31], [32]. The tri-nucleotide were predominant in Clementine mandarin, in agreement with other SSR survey studies [33] supporting the relative distribution of motifs in these plant groups.…”
Section: Discussionsupporting
confidence: 90%
“…. Total 3,648 pairs of primers were designed using Primer340 according to Ueno et al 41. and 480 pairs were screened for the detectability of polymorphisms between the F1 parents by 10.0% PAGE (Poly-Acrylamide Gel Electrophoresis).…”
Section: Methodsmentioning
confidence: 99%